Seed color represents salt resistance of alfalfa seeds (Medicago sativa L.): Based on the analysis of germination characteristics, seedling growth and seed traits - Xie, Jin; Li, Yao; Jiang, Gaoqian; Sun, Hongyong; Liu, Xiaojing; Han, Lipu (Frontiers in Plant Science, 2023)
Alfalfa (Medicago sativa L.) has significant feed value and ecological improvement function of marginal land. The difference in the maturity period of seeds in the same lots may be a mechanism of environmental adaptation. Seed color is a morphological trait associated with seed maturity. A clear understanding of the relationship between the seed color and seed stress resistance is helpful for seed selection for marginal land. This study evaluated the seed germination parameters (germinability and final germination percentage) and subsequent seedling growth (sprout height, root length, fresh and dry weight) of alfalfa under different salt stress, measured the electrical conductivity, water uptake, seed coat thickness, and endogenous hormone content in alfalfa seeds with different colors (green, yellow and brown). The results showed that seed color significantly influenced the seed germination and seedling growth. The germination parameters and seedling performance of brown seeds were significantly lower than that of green and yellow seeds under different salt stress. The germination parameters and seedling growth of brown seed declined most obviously with the aggravation of salt stress. The results suggested that brown seeds were less resistant to salt stress. Seed color had a significant effect on electrical conductivity, and it indicated that the yellow seeds had higher vigor. The seed coat thickness of various colors did not differ significantly. The seed water uptake rate and hormone content (IAA, GA3, ABA) in brown seeds were higher than that in green and yellow seeds, while the (IAA+GA3)/ABA in yellow seeds were higher than green and brown seeds. The alterations in seed germination and seedling performance among seed colors are likely due to the combination effect of the content and balance between IAA+GA3 and ABA. These results could improve the understanding of stress adaptation mechanisms of alfalfa and provide a theoretical basis for screening alfalfa seeds with high stress resistance.